2022
DOI: 10.7189/jogh.12..04005
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of turnover intention and influencing factors among emergency physicians: A national observation

Abstract: Background High turnover among physicians in emergency department is a great challenge in China. However, the rate and the reasons why physicians intend to leave have not been extensively studied yet. Therefore, this study aimed to identify the risk factors of turnover intention among physicians in emergency department. Methods A national cross-sectional survey was conducted from July to August 2018 in China. A total of 10 457 physicians in emergency department were inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 36 publications
0
17
0
Order By: Relevance
“…According to a recent Lancet study, the Middle East and North Africa are lacking 636,000 doctors, with South Asia having the biggest gaps (GBD 2019 Human Resources for Health Collaborators, 2022). Also, turnover intentions have been reported in close to 50% of physicians in emergency department, resident physicians and village doctors in China (Chen et al, 2022;Feng et al, 2022;Sun et al, 2022a); more than 50% health professionals in Ethiopia (Mekonnen et al, 2022); more than 55% doctors in Iraq and 30% doctors in South Korea (Hou et al, 2021). Burnout among healthcare workers and deteriorating care quality are the immediate effects (De Hert, 2020;Džakula & Relić, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…According to a recent Lancet study, the Middle East and North Africa are lacking 636,000 doctors, with South Asia having the biggest gaps (GBD 2019 Human Resources for Health Collaborators, 2022). Also, turnover intentions have been reported in close to 50% of physicians in emergency department, resident physicians and village doctors in China (Chen et al, 2022;Feng et al, 2022;Sun et al, 2022a); more than 50% health professionals in Ethiopia (Mekonnen et al, 2022); more than 55% doctors in Iraq and 30% doctors in South Korea (Hou et al, 2021). Burnout among healthcare workers and deteriorating care quality are the immediate effects (De Hert, 2020;Džakula & Relić, 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The study found a positive correlation between positive affect in individuals, such as pride and determination and citizenship behaviour, however, leadership affect was not addressed (Wang et al 2021). Similarly, a study by Feng et al (2022), included positive affect of emergency physicians as one factor that was directly associated with lower turnover intentions. In a conceptual paper by Reyes et al (2020), the importance of leaders maintaining a positive affect during crisis situations was highlighted in order to convey optimism, openness and confidence.…”
Section: Positive Affect Leadership and Emergency Servicesmentioning
confidence: 91%
“…Organizational commitment was measured according to the Organizational Commitment Scale developed by Mowday et al ( 22 24 ). This scale has been used in several studies to describe physicians' perceived association and loyalty to the organization and has proven good reliability ( 23 ).…”
Section: Methodsmentioning
confidence: 99%